# derivatives

posted by .

x^2cosx-2xsinx-2cosx

• derivatives -

I assume that you want the derivative, since you titles your post that way.

if y = x^2cosx-2xsinx-2cosx
dy/dx = (x^2)(-sinx) + 2x cosx - 2x(-cosx) - 2sinx + 2sinx
= -x^2( sinx) + 4x( cosx)

etc if needed

• derivatives - oops -

d/dx sinx = cosx

• derivatives -

yup!
sloppiness on my part

## Similar Questions

1. ### Trig

prove the identity (sinX)^6 +(cosX)^6= 1 - 3(sinX)^2 (cosX)^2 sinX^6= sinx^2 ^3 = (1-cosX^2)^3 = (1-2CosX^2 + cos^4) (1-cosX^2) then multiply that out 1-2CosX^2 + cos^4 - cosX^2 + 2cos^4 -cos^6 add that on the left to the cos^6, and …
2. ### Math - Solving for Trig Equations

For the following equation, why cannot I not solve it?
3. ### math

tanx+secx=2cosx (sinx/cosx)+ (1/cosx)=2cosx (sinx+1)/cosx =2cosx multiplying both sides by cosx sinx + 1 =2cos^2x sinx+1 = 2(1-sin^2x) 2sin^2x + sinx-1=0 (2sinx+1)(sinx-1)=0 x=30 x=270 but if i plug 270 back into the original equation …
4. ### trig

prove that (2cosx+1)(2cosx-1)= 1 +2cos2x
5. ### RESPONSE to PreCalc Question

h t t p : / / w w w . j i s k h a . c o m / d i s p l a y . c g i ?
6. ### Calculus

Determine the concavity and find the points of inflection. y=2cosx + sin2x 0≤x≤2pi y'=-2sinx + 2cos2x y"=-2cosx-4sinx How do I find the IP(s)?
7. ### Maths Calculus Derivatives & Limits

Using the definition of the derivative evaluate the following limits 1) Lim h---> 0 [ ( 8 + h )^1/3 - 2 ] / h 2) Lim x ---> pi/3 ( 2cosx - 1 ) / ( 3x - pi)
8. ### Math

Find the limit of (2cosx+3cosx-2)/(2cosx-1)as x tends to pi/3.
9. ### Pre Calculus

Having trouble verifying this identity... cscxtanx + secx= 2cosx This is what I've been trying (1/sinx)(sinx/cosx) + secx = 2cosx (1/cosx)+(1/cosx) = 2 cosx 2 secx = 2cosx that's what i ended up with, but i know it's now right. did …
10. ### Calculus

Just got through with derivatives, power rule, and chain rule. I am supposed to find the first and second derivatives of the function. y = 4x/√x+1 and y = cos^2(x) y' = [(x+1)^(1/2)(4)]-[(4x)(1/2(x+1)^(-1/2))(1)] y' = [4(x+1)^(1/2)-4x]/[2(x+1)^(1/2)(x+1)] …

More Similar Questions